Methods Of Developing Functional Literacy Of Students In Class 10-11 Mother Language Lessons - Bakayeva Rayxon Izatovna (Open Academia, 2024)
This paper explores various methods for enhancing functional literacy among students in Class 10-11 through mother language lessons. Functional literacy, which goes beyond basic reading and writing skills, encompasses the ability to comprehend, analyze, and apply information in real-world contexts. Recognizing the importance of mother language instruction in fostering deep understanding and critical thinking, this study examines strategies to optimize the teaching and learning process. Drawing on educational research and pedagogical practices, it proposes a range of effective approaches tailored to the specific needs and capabilities of students at this academic level. By integrating these methods into the curriculum, educators can empower students to become proficient and confident users of their mother tongue, thereby laying a strong foundation for lifelong learning and academic success.
Keywords: functional literacy; mother language; class 10-11; education